MANIPULASI LABA RIIL: UPAYA UNTUK MENGHINDARI KERUGIAN - Sari, Gustin Padwa (JURNAL AKUISISI, 2015)
This study aims to determine the practice of real earnings manipulation to avoid losses. This study uses four proxy of earnings manipulation that abnormal operating cash flow , abnormal production costs ,abnormal discretionary expenses, and real manipulation combinations. This research used sample on manufacturing companies listed on the Indonesia Stock Exchange among 2010-2012 by using purposive sampling method. Sample used in this study were 104 firm-years observation. This research using multiple regression analysis. Grouping the sample companies Identified allegedly manipulating profit and not identified earnings manipulation using EPS distribution. EPS based distribution rupiah exchange rate against the US $. The test results show This study provides empirical evidence that many companies perform real earnings management to increase the companys operating cash flow and increase the cost of production to avoid losses. Key words: Abnormal Operating Cash Flow , Abnormal Production Costs ,Abnormal Discretionary Expenses, Real Manipulation Combinations,Prospect Theory, Manufakturing Companies.